2018
DOI: 10.3390/w10101340
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Light Utilization and Yield of Rice under Rain-Catching and Controlled Irrigation

Abstract: In the middle and lower reaches of the Yangtze River, the rainfall is greater in summer. The technology of rain catching and controlled irrigation of rice help to save water by raising the water depth of the field after rain while the soil water content during the rest period is maintained at 70–100% of field capacity. The objectives of this study were to evaluate rice growth, canopy light utilization, and yield of rice under different rain-catching and controlled irrigation modes (T1: light drought and low st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
3
0
1
Order By: Relevance
“…Some researchers found that appropriate degree of AWD obtained similar or increased grain yields by 9~18% compared to FI [37,[39][40][41]. However, the inappropriate control of dryness under AWD could cause reductions in rice yields [13,37,39]. The performance in rice yield in our experimental results showed good agreement with the results above.…”
Section: Water Condition and Rice Yieldsupporting
confidence: 87%
See 3 more Smart Citations
“…Some researchers found that appropriate degree of AWD obtained similar or increased grain yields by 9~18% compared to FI [37,[39][40][41]. However, the inappropriate control of dryness under AWD could cause reductions in rice yields [13,37,39]. The performance in rice yield in our experimental results showed good agreement with the results above.…”
Section: Water Condition and Rice Yieldsupporting
confidence: 87%
“…As a result, the DP-SM has the highest irrigation water productivity, inducting the best use of water resources in a context of water scarce conditions. Some researchers found that appropriate degree of AWD obtained similar or increased grain yields by 9~18% compared to FI [37,[39][40][41]. However, the inappropriate control of dryness under AWD could cause reductions in rice yields [13,37,39].…”
Section: Water Condition and Rice Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…A. Malai abnormal bulir tersangkut pelepah daun bendera, B. Pelepah daun bendera patah (panah), C. Malai bergerombol, D. Bulir berisi embun air (panah) 2020). MenurutLu et al (2018) padi yang memiliki daun lebih tegak lebih tahan deraan hujan.…”
unclassified